1976
DOI: 10.3382/ps.0551830
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Transmission of Turkey Herpesvirus to Chickens

Abstract: Airborne transmission of turkey herpesvirus (HVT) between chickens was studied in two trials using an experimental line of White Leghorns. HVT either did not spread or spread poorly to chickens that had been exposed for 8 weeks to the exhaust air from a cage containing donor chickens inoculated with HVT at 8 weeks of age. There was no airborne transmission of HVT to chickens that had been exposed for 4 weeks. This study indicated a possible by an infrequent spread of HVT between chickens via airborne route.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…HVT vaccinal virus itself does not transmit laterally to chickens and was not thought to be shed in feather dander (Cho & Kenzy, 1975;Cho, 1976) until recent reports of significant shedding . Indeed, recent developments in technology have meant that all three MDV serotypes can be precisely quantified using real-time quantitative polymerase chain reaction (PCR) from tissues, feathers and poultry dust (Islam et al, 2004(Islam et al, , 2006aBaigent et al, 2005a,b;Abdul-Careem et al, 2006;Renz et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…HVT vaccinal virus itself does not transmit laterally to chickens and was not thought to be shed in feather dander (Cho & Kenzy, 1975;Cho, 1976) until recent reports of significant shedding . Indeed, recent developments in technology have meant that all three MDV serotypes can be precisely quantified using real-time quantitative polymerase chain reaction (PCR) from tissues, feathers and poultry dust (Islam et al, 2004(Islam et al, , 2006aBaigent et al, 2005a,b;Abdul-Careem et al, 2006;Renz et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Egg transmission of HVT does not occur Paul et al, 1972). HVTspreads by the airborne route from turkeys to turkeys, and from turkeys to chickens , but only poorly from chickens to chickens owing to poor replication in feather-follicle epithelium of this species (Cho, 1975(Cho, , 1976b.…”
Section: A Spread Of Infectionmentioning
confidence: 98%
“…The VP2 gene from a donor IBDV is inserted into the genome of the HVT vaccine, which expresses the protein of IBDV as it replicates, thus inducing IBDV protection in the vaccinated animal. Studies demonstrated that HVT did not spread or spread poorly to chickens that had been exposed [6][7], so despite its safe and high efficacy [8], the HVT-vectored IBD vaccines do not have the same potential to produce lateral immunization by horizontal transmission the way IBD live vaccines do. All told, these very different IBD vaccine technologies, when used over time, require constant monitoring of the field challenge due to their differing features and mechanisms of action.…”
Section: Description Of Problemmentioning
confidence: 99%